2011
DOI: 10.2495/sdp-v6-n2-195-211
|View full text |Cite
|
Sign up to set email alerts
|

Pasture for horses: an underestimated land use class in an urbanized and multifunctional area

Abstract: This paper investigates the spatial importance of horses in a multifunctional and urbanized area. The growing spatial importance of horses in the open space was already mentioned by different authors, but never quantifi ed before. In many countries, including Belgium, statistics on horses are only partly covered by agricultural data. As a consequence, the amount of space in use for horses, especially hobby horses, is largely unknown but may encompass a signifi cant area of the open space. Especially within the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 17 publications
0
36
0
1
Order By: Relevance
“…In an observational study of managed grasslands, paddocks grazed by horses were more species-rich and contained more indicator species for a 'high nature value' than paddocks grazed by cattle (Schmitz and Isselstein, submitted to this special issue). However, conflicts due to inappropriate grazing management by some horse farmers [21,22] are increasing, particularly in peri-urban regions. Experimental studies on agricultural grassland management with domestic horses are sparse [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In an observational study of managed grasslands, paddocks grazed by horses were more species-rich and contained more indicator species for a 'high nature value' than paddocks grazed by cattle (Schmitz and Isselstein, submitted to this special issue). However, conflicts due to inappropriate grazing management by some horse farmers [21,22] are increasing, particularly in peri-urban regions. Experimental studies on agricultural grassland management with domestic horses are sparse [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the knowledge on the equine locomotion behaviour, in particular, is derived from behaviour of feral horses in largely natural surroundings [27][28][29]. Anecdotal knowledge and observations of farmers question the applicability of those findings on domestic horses on pasture [21,22]. In comparison to other livestock, horses are well known for their specific and highly developed need for locomotion [30].…”
Section: Introductionmentioning
confidence: 99%
“…These lots are often difficult to access, making them less interesting for productive agriculture and more attractive for private users. Another recent study of Bomans et al (2011) analysed the spatial importance of the horse sector. Based on a random field survey they concluded that small parcels close to gardens and/or woods have a significantly higher chance to be used for (mainly private) horse keeping.…”
mentioning
confidence: 99%
“…Adding our work to studies collecting on spatial data of similar encroaching land uses, like the non-agricultural re-use of former agricultural buildings (Verhoeve et al, 2012) and horsification (Bomans et al, 2011a;Zasada, Berges, Hilgendorf, & Piorr, 2013), illustrates the importance of collecting empirical spatial data as a trigger to get them on the agendas of policy and research. Fragmentation and urbanization bring along challenging tasks in Europe (Tavares et al, 2012).…”
Section: Gardens In the Planning Picturementioning
confidence: 96%